Incorporating earned value management into income statements to improve project management profitability and elevate application in the business and management - Rudy Setyopurnomo; Sudarso Kaderi Wiryono; Yuliani Dwi Lestari; Subiakto Sukarno (PLoS ONE, 2025)
Our goal is to improve Project Management (PM) profitability and reduce discrepancies in information among stakeholders, which can result in conflicts. This will be accomplished by incorporating Earned Value Management (EVM) with the Income Statement and incorporating earnings before interest, tax, depreciation, and amortization (EBITDA) with the work breakdown structure (WBS). These incorporations will streamline information sharing between PM, other management professionals, and the stakeholders, ultimately fostering the application of PM within broader business and management contexts. We drew on theories from Project, Operations, Financial Management, Agency Theory, and the Theory of Performance Frontiers. We conducted multiple case studies in a shipbuilding corporation with 25 projects and an aircraft manufacturing corporation with 20 projects. Our analysis involved both qualitative and quantitative methods, ensuring the accuracy and practicality of our hypotheses and instilling confidence in our research findings. This integration addresses the information gap on profitability for non-project management professionals, empowering stakeholders to enhance project performance. This integration benefits the company by allowing the project manager and stakeholders to gain real-time insights into the project’s profitability, which enables continuous optimization of daily EBITDA by improving efficiency and productivity to achieve the project’s profitability target. This study and its innovative findings originate from the author’s unique approach, which is a significant contribution to the field of Project Management. This research focused on project management using EVM in for-profit organizations. Integrating EVM in the income statement also facilitates PM application in other management systems.